1994
DOI: 10.1021/j100078a015
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Chloride Ions with Chlorine Nitrate and Its Implications for Stratospheric Chemistry

Abstract: We present experimental and theoretical evidence for the rapid gas-phase reaction of C1-with ClONO2 to form C12 and Nos-. The reaction was studied in a Fourier-transform ion-cyclotron-resonance mass spectrometer, and a reaction rate constant of k = (9.2 f 3.0) X 10-lo cm3 s-l molecule-' at 298 K was determined. This value was -60% of the rate constant estimated from ion-dipolecollision theory. We also performed ab initiocalculations at the level of second-order Maller-Plesset perturbation theory using diffuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 7 publications
5
47
0
Order By: Relevance
“…This reaction has been shown to be thermodynamically favorable in the gas phase. 44 Wincel et al 30 have also shown reaction 3 to occur efficiently at temperatures…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This reaction has been shown to be thermodynamically favorable in the gas phase. 44 Wincel et al 30 have also shown reaction 3 to occur efficiently at temperatures…”
Section: Introductionmentioning
confidence: 97%
“…52,53 The direct reactivation of ClONO 2 has been of some interest theoretically. Haas et al 44 found no barrier for the gas-phase reaction with the chloride anion (eq 3), whereas Mebel et al 54 found that the barrier for the gas-phase reaction with molecular HCl (∼45-60 kcal mol -1 ) became negative when catalyzed by NO 3 -. Bianco and Hynes 43 reported the results of ab initio calculations for the direct reaction on a model ice lattice containing nine water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with another real possibility in which the excess proton has transferred far from the ClONO 2 reaction site, such that the ice surface reaction would be studied previously in the gas phase. 11 The eq I.1 vs eq I.4 issue has not been directly addressed experimentally, but an initial CIP scenario is supported by recent work 12 indicating that a hydrated proton tends to remain in the neighborhood of an ice surface, and in any event it explicitly addresses the issue of acidic conditions at the ice surface. We will return to the alternate route (eq I.4) issue at the conclusion of this Letter.…”
Section: Introductionmentioning
confidence: 99%
“…However, since molecular HOC1 has a relatively long residence time on the surface at low temperature, it has recently been demonstrated that it may react with adsorbed C1-to release chlorine gas : [Burley and Johnston, 1992]. Okumura et al have also proposed a similar SN2-type reaction mechanism for a possible direct reaction route of the gas phase chloride ion with chlorine nitrate, rather than via HOC1 [Haas et al, 1994]…”
Section: Introductionmentioning
confidence: 99%